2016
DOI: 10.1186/s40478-016-0295-6
|View full text |Cite
|
Sign up to set email alerts
|

X-linked intellectual disability gene CASK regulates postnatal brain growth in a non-cell autonomous manner

Abstract: The phenotypic spectrum among girls with heterozygous mutations in the X-linked intellectual disability (XLID) gene CASK (calcium/calmodulin-dependent serine protein kinase) includes postnatal microcephaly, ponto-cerebellar hypoplasia, seizures, optic nerve hypoplasia, growth retardation and hypotonia. Although CASK knockout mice were previously reported to exhibit perinatal lethality and a 3-fold increased apoptotic rate in the brain, CASK deletion was not found to affect neuronal physiology and their electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(88 citation statements)
references
References 70 publications
(94 reference statements)
5
83
0
Order By: Relevance
“…3 C). Indeed, we have previously documented that CASK promotes postnatal brain growth in a non-cell autonomous manner 24 (i.e., CASK + and CASK − cells are equally affected). We therefore tested if there is specific loss of only CASK negative axons in CASK (+/−) mice.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…3 C). Indeed, we have previously documented that CASK promotes postnatal brain growth in a non-cell autonomous manner 24 (i.e., CASK + and CASK − cells are equally affected). We therefore tested if there is specific loss of only CASK negative axons in CASK (+/−) mice.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, we documented that CASK (+/−) mice exhibit secondary microcephaly, disproportionate cerebellar hypoplasia, as well as thinning and hypoplasia of the optic nerve indicating that it recapitulates the human phenotypes associated with CASK mutation or loss. 24 We examined optic nerves following toluidine blue staining of semithin cross-sections—a method that labels myelin and allows the quantification of myelinated retinal axons in the ON. Surprisingly, besides being small ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ophthalmological abnormalities include hyperopia, strabismus, astigmatism and nystagmus. Constitutive knockout mice ( Cask − /y and Cask − /− ) die within the first day after birth,75 but deletion of a single Cask allele ( Cask +/ − ) in female mice has been found to recapitulate many human phenotypes, including microcephaly, hypotonia, ataxia and ONH without microphthalmia or malformation of the brain midline 79. The study suggested that Cask regulates oxidative metabolism in the brain, and the rate of glucose oxidation was reduced by 20% in the brain of Cask +/ − mice compared with wild-type littermates 79…”
Section: Introductionmentioning
confidence: 99%
“…Reports of XCI in adult human tissues did not indicate CASK as likely XCI escape gene (Tukiainen et al, 2017). Heterozygous CASK knockout mice that recapitulate the MICPCH phenotype showed CaskWT expression in 50% of neurons suggesting that XCI is stable in CASK-negative neurons (Mori et al, 2019;Srivastava et al, 2016). The stability of XCI during iPSC re-programing varies between protocols, and activation of both X chromosomes with subsequent random silencing of one X has been observed (Dandulakis et al, 2016).…”
Section: Cask-related Disorders Have Emerged As An Important Genetic mentioning
confidence: 99%